The effect of differences in silvofishery pond types and gender on the growth performance of mud crabs (Scylla serrata) - Asep Akmal Aonullah; Annisa Bias Cahyanurani; Andina Chairun Nisa; Diana Putri Renitasari; Asthervina Widyastami Puspitasari; Aditya Brahmana (Depik, 2025)
Mangrove crabs are one of the important fisheries commodities in Indonesia which have made a significant contribution to the lives of coastal communities. This study aims to analyze differences in growth performance of mud crabs reared in different silvofishery ponds to find out the effect of gender and to determine the interaction patterns between silvofishery pond type and gender. This research method uses a Factorial Randomized Block Design (FRBD) which consists of two factors, namely pond type (core pond, trench pond) and sex (male, female) so that it has 6 treatment combinations and 3 replications for each treatment. The initial weight of the test mud crab was 70-75 g. Test animals were kept for 56 days in crab baskets. The results showed that the interaction between pond type and sex had a significant influence on daily growth rate and absolute weight growth but did not significantly influence the feed conversion ratio and feed utilization efficiency. Duncan's further tests showed that the type of pond had a real influence on the feed conversion ratio and feed utilization efficiency. The best Feed Conversion Ratio was found in the core pond treatment with 3.80 1.05 with the highest feed utilization efficiency of 27.67 3.23 %.The survival rate shows values that are not significantly different between all treatments (86.67 100%.). The water quality measurement values during the research were still optimal for the growth of male and female mud crabs. Treatment of core ponds with female crabs (T2K2) showed the best performance in terms of daily growth rate and absolute weight growth of mud crabs. Core pond treatment with female crabs showed the highest daily growth results of 0.82% 0.01% and absolute growth of 42.00 1.00.Keywords:Mud crabSilvofisheryCore PondDitch PondGenderGrowth